Eating`s cheating and the peculiarity of male professional road cycling - Brittain, J. J. (Sport in Society: Cultures, Commerce, Media, Politics, 2026)
Itself a unique outlier when related to for-profit sport, contemporary professional male road cycling also provides a subject that can be framed as an outsider. Where most high-performance sports applaud expressions of visible musculinity, the peloton demarcates power not through strength-as-observable but rather the absence thereof. Through an inversion of meaning, the most dominant are the most diminished. Here, those who embody the greatest qualitative and quantitative representations of success exhibit a physique more akin to a pre-pubescent boy than chiseled Adonis. Through a critique of capital and the sport`s normalizing of disordered eating, the work centres the pro male road cyclist as an under-regarded but noteworthy sociality. Of broad value to the fields of applied, physical, and social science, the work tracks how those, if to succeed, are compelled to take up a different depiction of the elite athlete. When weighed against others, this cohort`s professional relation to power, food, and gender interrupts certain expectations, constructions, and constitutions that signal the need for such a sociological analysis of cycling`s current practices and their impacts.